Palytoxin acts on Na(+),K(+)-ATPase but not non-gastric H(+),K(+)-ATPase - Guennoun-Lehmann, Saida (2007)
Palytoxin (PTX) opens a pathway for ions to pass through Na,K-ATPase. We investigate here whether PTX also acts on non-gastric H,K-ATPases. The following combinations of cRNA were expressed in Xenopus laevis oocytes: Bufo marinus bladder H,K-ATPase α(2)- and Na,K-ATPase β(2)-subunits; Bufo Na,K-ATPase α(1)- and Na,K-ATPase β(2)-subunits; and Bufo Na,K-ATPase β(2)-subunit alone. The response to PTX was measured after blocking endogenous Xenopus Na,K-ATPase with 10 μM ouabain. Functional expression was confirmed by measuring (86)Rb uptake. PTX (5 nM) produced a large increase of membrane conductance in oocytes expressing Bufo Na,K-ATPase, but no significant increase occurred in oocytes expressing Bufo H,K-ATPase or in those injected with Bufo β(2)-subunit alone. Expression of the following combinations of cDNA was investigated in HeLa cells: rat colonic H,K-ATPase α(1)-subunit and Na,K-ATPase β(1)-subunit; rat Na,K-ATPase α(2)-subunit and Na,K-ATPase β(2)-subunit; and rat Na,K-ATPase β(1) or Na,K-ATPase β(2) subunit alone. Measurement of increases in (86)Rb uptake confirmed that both rat Na,K- and H,K-pumps were functional in HeLa cells expressing rat colonic HKα(1)/NKβ(1) and NKα(2)/NKβ(2). Whole-cell patch clamp measurements in HeLa cells expressing rat colonic HKα(1)/NKβ(1) exposed to 100 nM PTX showed no significant increase of membrane current and there was no membrane conductance increase in HeLa cells transfected with rat NKβ(1) or rat NKβ(2) subunits alone. However, in HeLa Cells expressing rat NKα(2) NKβ(2), outward current was observed after pump activation by 20 mM K(+) and a large membrane conductance increase occurred after 100 nM PTX. We conclude that non-gastric H,K-ATPases are not sensitive to palytoxin when expressed in these cells whereas palytoxin does act on Na,K-ATPase.